Austro-Prussian War of 1866, Landscape Archaeology of the Battlefield of Sadowa-Königgrätz - Holas, Matouš (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2023)
The article attempts to present current results of landscape archaeology concerning a military conflict between Prussia and Austria in the summer of 1866 near Hradec Králové (Sadowa/Königgrätz). The aim is to introduce the possibilities of analysing individual available sources using the methods of battlefield archaeology, which is a sub-discipline of post-medieval archaeology. The historical period in question is not only a regional issue. This topic is mainly important with regard to protection of constantly endangered war relics, whose number in East Bohemia has been increasing in the past decade. The knowledge acquired from systematic and rescue excavations conducted in various parts of battlefields in the territory of Hradec Králové region demands new analysis to be appropriately evaluated and interpreted. The primary processing and treatment of finds are equally important as their spatial information and a successful setting into the chronological frame of well-known historical events. Archaeological knowledge thus sheds a new light on these events. The paper presents basic research topics and methods, to which increased attention is currently being paid within the context of archaeological sites. All of them use a wider view of the 1866 historical landscape, which was not distinctly modified for the purpose of military operations, but on the contrary significantly influenced their course and sequence. In order to properly interpret the acquired spatial data, it is necessary to reconstruct this historical landscape and to define the form of various activities which took place there during the war.
il. ; 24 cm
Keywords: Battlefield archaeology; landscape archaeology; Austro-Prussian War of 1866; 1866 War archaeology